The Relation Between Organizational Culture and Strategy in Hospitals: Mini-Review - Alsaqqa, Hatem H (Borong Newinera Publisher, 2024)
Regardless of how people define culture, most experts believe that having a strong culture is beneficial to any organization. Hospital X devised and executed a new organizational strategy in order to become prospective. During this procedure, hospitals’ management paid less attention to organizational culture, leading to the assumption that hospital’s culture is incompatible with the strategy. However, in order to make a successful transformation and implement a strategy, a suitable culture must be established. Based on a comparison of the strategic enablers with the cultural dimensions, it appears that the six cultural dimensions proposed by Cameron and Quinn should contain the necessary cultural circumstances. In order for the intended hospital’s strategy to be more successful and efficient, it must be implemented in accordance with the intended organizational culture. To assess the impact of culture on hospital’s strategy, it must concentrate on strategic enablers. It is predicted that focusing on strategic enablers will suffice in identifying a comprehensive strategy concept. The cultural circumstances of the factors that drive each strategic enabler possibly will be added to each strategic dimension. In order to attain the strategic enabler, these conditions must be met. As a result, a more culturally aware hospital’s strategy will emerge.